The differences in severity of temporomandibular joint disorder before and after orthognathic surgery - Akmalia Hardini; Endang Sjamsudin; Abel T. Yuza; Seto A. Sadputranto (Journal of Dentomaxillofacial Science, 2022)
Objective: The aim of this study was to analyze the differences in the severity of Temporomandibular Joint (TMJ) disorders before and after orthognathic surgery. Material and Methods: This type of research is analytical observation with 10 subjects, who will perform orthognathic surgery at the Oral and Maxillofacial Surgery section in the Dental and Oral Hospital and Hasan Sadikin Hospital, then perform TMJ clinical examination with the Helkimo index, filling out the Fonseca questionnaire before and after orthognathic surgery and Cone Beam Computed Tomography (CBCT) photos 7 months after orthognathic surgery. Statistical analysis using paired data test (Wilcoxon test). Results: The results of the paired data test calculation showed that there was a difference in the degree of severity before and after surgery which was statistically significant with results-p <0.05 where after surgery there was a decrease in the severity of TMJ with using the Helkimo index and the Fonseca questionnaire. Conclusion: Orthognathic surgery can reduce the severity of temporomandibular joint disorders, assessed by Helkimo index and Fonseca questionnaire.